2023
DOI: 10.5603/cj.a2021.0065
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with takotsubo syndrome versus spontaneous coronary artery dissection

Abstract: Clinical characteristics and outcomes of patients with takotsubo syndrome versus spontaneous coronary artery dissectionVictoria L. Cammann et al., Takotsubo syndrome vs. spontaneous coronary artery dissection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…A major difference between these two clinical entities is the large age gap that explain how differently these syndromes are perceived in real-world clinical settings. The age distribution in our SCAD and TTS groups is comparable to that found in previous registries [11,12,17,18]. Hypertension, dyslipidemia, and diabetes were more common in the TTS group.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A major difference between these two clinical entities is the large age gap that explain how differently these syndromes are perceived in real-world clinical settings. The age distribution in our SCAD and TTS groups is comparable to that found in previous registries [11,12,17,18]. Hypertension, dyslipidemia, and diabetes were more common in the TTS group.…”
Section: Discussionsupporting
confidence: 87%
“…This subset of TTS patients has been previously associated with a worse prognosis as compared to primary forms of TTS and this may also explain the adverse in-hospital and long-term prognosis of our TTS patients [27,28]. In line with some previous studies, emotional stress triggers were more frequently seen among SCAD patients than in TTS (also known as 'stress cardiomyopathy') [8,12]. Besides and importantly, SCAD group had a higher prevalence of depression disorder with no difference in previous history of anxiety disorder.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Patients with TS have worse in-hospital complications and outcomes including a higher risk of mortality during the index admission compared with SCAD [43]. Cammann et al [46] reported that left ventricular ejection was more impaired in TS compared to SCAD. In addition, 30-day mortality was significantly higher in TS patients in the same study.…”
Section: Association Of Scad and Takotsubo Syndromementioning
confidence: 99%
“…It was with interest that the present authors read an article by Victoria L. Cammann et al [ 1 ], who compared clinical features and outcomes in patients with Takotsubo syndrome (TTS) and spontaneous coronary artery dissection (SCAD). The study compared the clinical characteristics and outcomes of 2098 TTS patients from the International Takotsubo Registry to 750 SCAD patients from the Canadian Spontaneous Coronary Artery Dissection Cohort Study.…”
mentioning
confidence: 99%